2016
DOI: 10.1002/ldr.2632
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon and Inorganic Carbon Accumulation Along a 30‐year Grassland Restoration Chronosequence in Semi‐arid Regions (China)

Abstract: Carbon accumulation is an important research topic for grassland restoration. It is requisite to determine the dynamics of the soil carbon pools [soil organic carbon (SOC) and soil inorganic carbon (SIC)] for understanding regional carbon budgets. In this study, we chose a grassland restoration chronosequence (cropland, 0 years; grasslands restored for 5, 15 and 30 years, i.e. RG5, RG15 and RG30, respectively) to compare the SOC and SIC pools in different soil profiles. Our results showed that SOC stock in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 63 publications
3
50
1
Order By: Relevance
“…Vegetation biomass plays a non‐negligible role in determining SOC stocks (L. F. Chen et al, ). Vegetation recovery on the Loess Plateau favours SOC sequestration (Deng, Liu, & Shangguan, ; Deng & Shangguan, ; Deng, Shangguan, Wu, & Chang, ; Liu, Dang, Tian, Wang, & Wu, ). Pearson correlation coefficients and associated significance levels were utilized to identify the relationship between grassland SOC and biomass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation biomass plays a non‐negligible role in determining SOC stocks (L. F. Chen et al, ). Vegetation recovery on the Loess Plateau favours SOC sequestration (Deng, Liu, & Shangguan, ; Deng & Shangguan, ; Deng, Shangguan, Wu, & Chang, ; Liu, Dang, Tian, Wang, & Wu, ). Pearson correlation coefficients and associated significance levels were utilized to identify the relationship between grassland SOC and biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang and Shangguan () studied the soil water content (SWC) in the Ziwuling forest region and found that grasslands exhibited a higher SWC than shrublands and forestlands. In addition, Liu et al () studied the Qiaozigou watershed and found that the SOC content in sediments was positively correlated with SWC ( p < .05). A high grassland SWC might favour SOC accumulation in mountain areas.…”
Section: Discussionmentioning
confidence: 99%
“…Grasslands can have a significant effect in arid and semiarid areas' C cycle through changing soil C accumulation rates and turnover, soil erosion, and vegetation biomass (Deng et al, 2014a;Liu et al, 2017). Plants regulate SOC stock by controlling, assimilating, and accumulating C in the plant root system, and then through plant respiration and leaching release from soil to atmosphere (De Deyn et al, 2008;Garcia-Diaz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Soil mineral nitrogen was the dominant source of plant uptake nitrogen [20], herbivores appeared to have a strong influence on grassland N availability, and some studies showed that grazing could lead to an increase in soil δ 15 N [15,19,21], while no apparent and negative effects of grazing have also been reported [22]. Ammonia volatilization and gaseous N losses via denitrification resulted in the remaining soil and plant enrichment of 15 N in grazed grasslands [12].…”
Section: Discussionmentioning
confidence: 99%